AMBIVALENSI TEKNOLOGI KOMUNIKASI DALAM FENOMENA GLOBAL VILLAGE VS GLOBAL PILLAGE - Vannyora Okditazeini (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This paper elaborates on how the development of communication media enables us to communicate with anyone, anywhere.